2017
DOI: 10.1038/s41598-017-06623-z
|View full text |Cite
|
Sign up to set email alerts
|

Virus and dsRNA-triggered transcriptional responses reveal key components of honey bee antiviral defense

Abstract: Recent high annual losses of honey bee colonies are associated with many factors, including RNA virus infections. Honey bee antiviral responses include RNA interference and immune pathway activation, but their relative roles in antiviral defense are not well understood. To better characterize the mechanism(s) of honey bee antiviral defense, bees were infected with a model virus in the presence or absence of dsRNA, a virus associated molecular pattern. Regardless of sequence specificity, dsRNA reduced virus abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
148
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(156 citation statements)
references
References 129 publications
(193 reference statements)
6
148
2
Order By: Relevance
“…We found that the RNAi and Imd pathways, as well as the JaK/STAT and JNK pathways, are down-regulated in the introduced range. In honey bees, the JaK/STAT and RNAi immune pathways are primarily directed against viruses, whereas the Toll, Imd and JNK pathways are more ubiquitous and associated with defence against bacteria and other pathogens (Evans et al 2006;Brutscher et al 2015Brutscher et al , 2017McMenamin et al 2018). Interestingly, genes associated with the Toll pathway in our results did not altogether show a clear range-specific expression pattern (i.e.…”
Section: Discussioncontrasting
confidence: 61%
“…We found that the RNAi and Imd pathways, as well as the JaK/STAT and JNK pathways, are down-regulated in the introduced range. In honey bees, the JaK/STAT and RNAi immune pathways are primarily directed against viruses, whereas the Toll, Imd and JNK pathways are more ubiquitous and associated with defence against bacteria and other pathogens (Evans et al 2006;Brutscher et al 2015Brutscher et al , 2017McMenamin et al 2018). Interestingly, genes associated with the Toll pathway in our results did not altogether show a clear range-specific expression pattern (i.e.…”
Section: Discussioncontrasting
confidence: 61%
“…Non‐target effects of dsRNA, however, might also be caused by other factors including a general immune stimulation or a saturation of the RNAi machinery as a consequence of the ingestion of high doses of dsRNA . While the latter has not yet been observed in invertebrates, dsRNA‐mediated immune responses have for example been reported for honey bees, bumble bees, and the silkworm …”
Section: Introductionmentioning
confidence: 99%
“…Non-target effects of dsRNA, however, might also be caused by other factors including a general immune stimulation or a saturation of the RNAi machinery as a consequence of the ingestion of high doses of dsRNA. 30,31 While the latter has not yet been observed in invertebrates, dsRNA-mediated immune responses have for example been reported for honey bees, 32,33 bumble bees, 34 and the silkworm. 35 Before a GE plant can be commercialized, its risk to valued components of the environment must be investigated in an environmental risk assessment (ERA), which includes an assessment of possible adverse effects on valued non-target organisms and on the ecosystem services they provide.…”
Section: Introductionmentioning
confidence: 99%
“…A number of molecular approaches, including at the levels of the transcriptome [26][27][28][29] and proteome 30,31 , have been applied to honeybees in efforts to understand the cellular mechanisms of Varroa resistance as well as to identify biomarkers of these traits. This is a daunting task due to the potential complexities of the molecular mechanisms underlying these phenotypes, coupled with the challenges of deciphering biology within a mixed genetic population.…”
mentioning
confidence: 99%